Comparison of APACHE II Score and SOFA Score for Predicting Survival Rate in ICU: A Systematic Review - Dananjaya, Vigyan; Adi Santika, Suparno (Faculty of Medicine, Universitas Jember, 2025)
Predicting mortality in critically ill patients is a key challenge in intensive care units (ICUs), and scoring systems such as SOFA (Sequential Organ Failure Assessment) and APACHE II (Acute Physiology and Chronic Health Evaluation II) are commonly used to estimate prognosis. This systematic review aimed to assess how accurately these two scoring systems predict ICU survival outcomes. The review was conducted in accordance with the PRISMA guidelines and registered on PROSPERO (CRD42024600239). Relevant studies published from 2014 to 2024 were identified through a comprehensive search of PubMed, ScienceDirect, SpringerLink, ProQuest, and the Cochrane Library. After screening 1,427 studies, 25 peer-reviewed articles met the inclusion criteria and were analyzed. The results consistently demonstrated that higher SOFA and APACHE II scores were significantly associated with increased mortality rates and prolonged ICU stays. The APACHE II score thresholds varied from 13 to 18.5, while SOFA score cutoffs ranged from 4.5 to 9. Several studies suggested that combining both scoring systems may enhance prognostic accuracy and inform clinical decision-making more effectively than either system alone. In conclusion, both SOFA and APACHE II scores are valid and dependable predictors of ICU mortality. Their combined use may improve risk stratification, support timely interventions, and optimize outcomes in critical care practice.